1992
DOI: 10.1007/bf02260907
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive profile of Alzheimer patients with extrapyramidal signs: A longitudinal study

Abstract: The cognitive profile of Alzheimer patients without (ADE-, n = 17) and with (AD, E+, n = 15) extrapyramidal signs (rigidity or bradykinesia), at the time of diagnosis, was examined in a 3-year follow-up study and compared to cognitive performance of demented (PD D+, n = 18) and nondemented (PD D-, n = 17) patients with Parkinson's disease and normal elderly controls (n = 19). Although the AD E+ and AD E- groups did not differ significantly at the initial testing, the AD E+ patients showed greater deterioration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The lack of statistical signi®cance for illness duration in any neuropsychological model of motor dysfunction suggests that the association between neuropsychological and motor functions in AD may be unrelated to degenerative processes that accumulate throughout the illness. The association characterized by more severe EPS and poorer cognitive performance is consistent with previous literature (Morris et al, 1989;Soininen et al, 1992a;Richards et al, 1993). This pattern was observed for EPS total score as well as EPS factor scores, but not for all cognitive ability areas.…”
Section: Discussionsupporting
confidence: 90%
“…The lack of statistical signi®cance for illness duration in any neuropsychological model of motor dysfunction suggests that the association between neuropsychological and motor functions in AD may be unrelated to degenerative processes that accumulate throughout the illness. The association characterized by more severe EPS and poorer cognitive performance is consistent with previous literature (Morris et al, 1989;Soininen et al, 1992a;Richards et al, 1993). This pattern was observed for EPS total score as well as EPS factor scores, but not for all cognitive ability areas.…”
Section: Discussionsupporting
confidence: 90%
“…In the other neuropsychological measures high scores indicate better performance and correlations with rCBF are positive Arie, 1994). Clinical experience has shown that the profile of cognitive deficits varies among AD patients (Soininen et al, 1992a). In this study, we used a cluster analysis on patients' performance on neuropsychological tests to identify AD subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics, prognosis, distribution and severity of the neuropathological and neurochemical alterations vary. Subgroups of AD patients were attempted to identify on the basis of early versus late onset of the disease, familial versus sporadic disease, EEG findings, occurrence of certain clinical features such as extrapyramidal signs, hallucinations, as well as qualitatively different profiles of cognitive impairment (Mayeux et al, 1985;Chui et al, 1985;Knesevich et al, 1985;Drachman et al, 1990;Helkala et al, 1991;Soininen et al, 1992a). Results of these studies have been inconsistent depending on differences in patient populations and methods.…”
Section: Introductionmentioning
confidence: 98%
“…In AD, individuals with extrapyramidal symptoms (Mayeux et al, 1985;Soininan et al, 1992) and those with visual hallucinations (Drevets and Rubin, 1989;Gilley et al, 1991;Rosen and Zubenko, 1991;F orstl et al, 1993) tend to decline more rapidly, although it has been reported that the association of cognitive decline with psychotic symptoms may be secondary to neuroleptic treatment (McShane et al, 1997). These are therefore important candidates of accelerated cognitive decline in DLB.…”
Section: Introductionmentioning
confidence: 94%